High-wear-resistance and high-tear-resistance tire tread rubber and preparation method thereof

By using graphene/N110 series carbon black/silica three-phase composite materials in tire tread rubber, combined with the preparation method of natural rubber and other additives, the existing tread rubber has solved the problems of wear resistance and complex road performance. By solving the shortcomings, we have achieved the preparation of tread rubber with high wear resistance and high tear resistance, with simple process and low cost.

CN119350726APending Publication Date: 2025-01-24GLOBAL GRAGHENE (QINGDAO) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411566276.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing tire tread glue has shortcomings in high wear resistance and complex road surface performance, the preparation process is complex and the industrial production cost is high.

Method used

The graphene/N110 is carbon black/white charcoal black three -phase composite material as a mixed powder, and is prepared with natural rubber, zinc oxide, aging agent, dispersion agent, promotent, and sulfur. Reinforcement and thin craftsmanship are made of high wear resistance and high tear tire tire tire gum.

Benefits of technology

The excellent performance of high wear resistance, high -tear resistance, tensile strength, and stretch of stretching of tire gum, simplifying the preparation process and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119330060000141
    Figure BDA0005119330060000141
  • Figure BDA0005119330060000151
    Figure BDA0005119330060000151
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber, and particularly relates to high-wear-resistance and high-tear-resistance tire tread rubber and a preparation method thereof. The high-wear-resistance and high-tear-resistance tire tread rubber is prepared from natural rubber, mixed powder, zinc oxide, an anti-aging agent, a dispersing agent, an accelerant, a scorch retarder and sulfur, the mixed powder is mainly prepared from graphene, carbon black and high-specific-surface white carbon black, the graphene, the carbon black and the high-specific-surface white carbon black are pretreated to obtain the mixed powder, and then the mixed powder is added into the tire tread rubber, so that the problems that the graphene, the N110 series carbon black and the high-specific-surface white carbon black are poor in dispersity in rubber and poor in processing technology are solved, and the service life of the tire tread rubber is prolonged. And the wear resistance, tear resistance and other mechanical properties of the tire tread rubber can be greatly improved. Meanwhile, the tread rubber is simple in preparation process, relatively low in cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and in particular relates to a highly wear-resistant and tear-resistant tire tread rubber and a preparation method thereof. Background Art

[0002] The tread rubber refers to the rubber material with patterns printed on the outermost layer of the tire that contacts the road surface. It can give the tire traction, cushion the impact and swing during driving, and prevent the cord layer from being cut and punctured. Therefore, the tread rubber is required to have high wear resistance, fatigue resistance, good aging resistance, high tensile strength, elasticity and toughness, and low heat generation during driving.

[0003] The current tire tread rubber, especially the mining tire tread rubber, is insufficient in adapting to the high wear resistance and performance required by complex road surfaces. Therefore, how to improve the international market competitiveness of products and how to improve the performance parameters of rubber will be the future research direction of the rubber industry.

[0004] Patent CN106279853B discloses a method for preparing a highly wear-resistant tire tread rubber, wherein graphene is oxidized in an ethanol environment, and then reacted with surfactants such as sodium dodecyl sulfate and sodium nitrate by hydrogen peroxide catalysis, and then mixed and calcined with silicon dioxide to obtain a tread rubber filler base material, which is then mixed and plasticized with epoxidized natural rubber and butadiene rubber, and then stearic acid, paraffin and other substances are added for mixing, and finally sulfur is added for mixing to obtain a highly wear-resistant tire tread rubber. However, this invention has the disadvantages of complex preparation process and high industrial production cost.

[0005] The patent application with the patent application number CN110713630A discloses a high wear-resistant tire tread rubber, which is made of the following raw materials in parts by weight: 80-90 parts of natural rubber, 15-25 parts of styrene-butadiene rubber, 10-20 parts of butadiene rubber, 10-20 parts of cis-isoprene rubber, 35-45 parts of high wear-resistant carbon black, 8-12 parts of white carbon black, 5-10 parts of zinc oxide, 1-3 parts of stearic acid, 1-2 parts of dispersant, 1-2 parts of plasticizer, 1-2 parts of silane coupling agent, 1-3 parts of antioxidant, 1-3 parts of microcrystalline wax, 0.5-1 parts of anti-scorch agent, and 1-2 parts of accelerator. The invention adopts conventional technology, but the performance of the tread rubber obtained is relatively poor. Summary of the invention

[0006] Based on the above technical background, the main purpose of the present invention is to provide a highly wear-resistant and tear-resistant tire tread rubber and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] The first aspect of the present invention is to provide a highly wear-resistant and tear-resistant tire tread rubber, which is prepared from the following raw materials in parts by weight: 100 parts of natural rubber, 70-80 parts of mixed powder, 4-6 parts of zinc oxide, 3-5 parts of antioxidant, 1-3 parts of dispersant, 1-3 parts of accelerator, 0.1-1 part of scorch retarder, and 1-2 parts of sulfur.

[0009] Preferably, the highly wear-resistant and tear-resistant tire tread rubber is made from the following raw materials in parts by weight: 100 parts of natural rubber, 74 to 79.6 parts of mixed powder, 5 parts of zinc oxide, 4 parts of antioxidant, 1.5 parts of dispersant, 2 parts of accelerator, 0.5 parts of anti-scorch agent, and 1.6 parts of sulfur.

[0010] Preferably, the mixed powder is made of graphene, carbon black, white carbon black, silane coupling agent, nano-sized zinc methacrylate, liquid rubber, and peroxide initiator;

[0011] The mass ratio of the graphene, carbon black, white carbon black, silane coupling agent, zinc methacrylate, liquid rubber and peroxide initiator is (3-10): (22-30): (18-27): (4-7): (3-9): (7-12): (0.3-0.7).

[0012] More preferably, the white carbon black has a specific surface area greater than 200 m 2 / g of white carbon black; and / or,

[0013] More preferably, the silane coupling agent is selected from one or more of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, bis-[γ-(triethoxysilyl)propyl]disulfide, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane; and / or,

[0014] More preferably, the liquid rubber is selected from one or more of liquid isoprene, liquid butadiene, liquid styrene butadiene, and liquid ethylene propylene; and / or,

[0015] More preferably, the peroxide initiator is selected from one or more of dicumyl peroxide, 1,4-di-tert-butylperoxycumene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0016] Preferably, the antioxidant is selected from one or more of N-cyclohexyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and 2-thiol benzimidazole; and / or,

[0017] Preferably, the dispersant is selected from one or both of microcrystalline wax and paraffin wax; and / or,

[0018] Preferably, the accelerator is selected from one or more of N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, 2-thiolbenzothiazole, diphenylguanidine, benzothiazole disulfide, and tetramethylthiuram disulfide; and / or,

[0019] Preferably, the scorch retarder is N-cyclohexylthiophthalimide.

[0020] The second aspect of the present invention is to provide a method for preparing the high wear-resistant and high tear-resistant tire tread rubber according to the first aspect of the present invention, the preparation method comprising the following steps:

[0021] Step 1, plasticizing the natural rubber, then adding zinc oxide, antioxidant, dispersant, accelerator, and anti-scorch agent for banburying, then adding the mixed powder for further banburying, and removing the rubber to obtain a film;

[0022] Step 2: Re-refining the rubber sheet obtained in step 1, then adding sulfur and accelerator to turn the rubber sheet left and right, and finally thinning it to obtain tire tread rubber.

[0023] In step 1, preferably, the mixed powder is prepared by the following steps:

[0024] Step a, adding graphene, carbon black and white carbon black into water and stirring to obtain a mixed solution, adding a silane coupling agent into a mixed solvent of ethanol, water and acetic acid, stirring to obtain a hydrolyzate, adding the hydrolyzate into the mixed solution to react, after the reaction is completed, filtering to obtain a solid, and drying to obtain a powder solid;

[0025] Step b: mixing and stirring the powder solid and zinc methacrylate, and then adding liquid rubber and peroxide initiator and continuing to stir and mix to obtain a mixed powder (three-phase composite material).

[0026] More preferably, in step a,

[0027] Adding graphene, carbon black and white carbon black into water, stirring and mixing at a stirring speed of 1500 to 2500 r / min and a temperature of 50 to 70° C. to obtain a mixed solution; and / or,

[0028] Mixing ethanol and water in a volume ratio of (150-250): (100-150), then adding acetic acid to adjust the pH to 3.5-4.5, slowly adding a silane coupling agent to the obtained mixed solvent, stirring at a stirring speed of 300-700 r / min until the solution becomes clear, to obtain a hydrolyzate; and / or,

[0029] Slowly adding the hydrolyzate to the mixed solution, reacting at 50-70° C. for 1-3 hours, filtering to obtain a solid, and then drying at 100-120° C. for 1-3 hours to obtain a powder solid; and / or,

[0030] More preferably, in step b, zinc methacrylate is added to the powder solid at 90-110° C. and a stirring speed of 2500-3500 r / min, and the mixture is mixed and stirred for 20-45 min, and then liquid rubber and peroxide initiator are added and the mixture is mixed and stirred for 20-45 min to obtain a mixed powder.

[0031] Preferably, the natural rubber is plasticized at 60-70 r / min and 60-80° C. for 1-3 min, and then zinc oxide, antioxidant, dispersant, accelerator and anti-scorch agent are added and kneaded for 1-3 min, and then the mixed powder is added and kneaded for 1-3 min, and the temperature is raised to 140-160° C. for debonding to obtain a rubber sheet.

[0032] In step 2,

[0033] Preferably, the roller spacing of the mixing mill is adjusted to 1-2 mm, the rubber sheet obtained in step 1 is re-refined 1-4 times, rolled, sulfur and accelerator are added, the rubber sheet is turned over 2-4 times on each side, and then the roller spacing of the mixing mill is adjusted to 0.1-0.3 mm and thinned 5-9 times to obtain tire tread rubber.

[0034] The beneficial effects of the present invention are:

[0035] (1) The present invention provides a highly wear-resistant and tear-resistant tire tread rubber, wherein the tread rubber is prepared by adding an easily dispersible graphene / N110 series carbon black / white carbon black three-phase composite material (i.e., mixed powder) to natural rubber, and then preparing the tread rubber together with zinc oxide, an antioxidant, a dispersant, an accelerator, a scorch retarder and sulfur. The obtained tire tread rubber has excellent properties of high wear resistance, high tear resistance, high tensile strength and high elongation at break.

[0036] (2) The graphene / N110 series carbon black / white carbon black mixed powder of the present invention is prepared by first treating the graphene / N110 series carbon black / white carbon black with a silane coupling agent to carry out a silanization reaction. The role of adding the silane coupling agent is that the alkoxy group at one end can undergo a hydrolysis reaction and undergo a condensation reaction with groups such as hydroxyl groups on the surface of the graphene / N110 series carbon black / white carbon black to form a chemical bond or a hydrogen bond, and the other end of the silane coupling agent can undergo a chemical reaction with the rubber matrix, thereby improving the dispersibility of the graphene / N110 series carbon black / white carbon black powder in the rubber matrix.

[0037] Then, the graphene / N110 series carbon black / high specific carbon white powder treated with the silane coupling agent is added to a high-temperature high-speed mixer, and then nano-sized zinc methacrylate, peroxide initiator and liquid rubber are added. Under the action of high temperature and high-speed stirring, the nano-sized zinc methacrylate is tightly adsorbed on the surface of the graphene / N110 series carbon black / high specific carbon white powder. At the same time, the zinc methacrylate on the surface of the graphene / N110 series carbon black / high specific carbon white powder forms a high-energy ionic bond with the liquid rubber under the action of the peroxide initiator, so that the liquid rubber is tightly coated on the graphene / N110 series carbon black / high specific carbon white powder. On the surface of N110 series carbon black / high specific surface white carbon black powder, the liquid rubber covers the graphene / N110 series carbon black / high specific surface white carbon black powder, thereby blocking the van der Waals force and Coulomb force between the materials, reducing or eliminating the agglomeration between them, and thus greatly improving the dispersibility of the graphene / N110 series carbon black / high specific surface white carbon black powder and improving its compatibility with rubber polymer materials; in addition, the liquid rubber that does not participate in the reaction in the liquid rubber can continue to participate in the vulcanization when reacting with other unvulcanized rubbers, which can further enhance the bonding force between the graphene / N110 series carbon black / high specific surface white carbon black mixed powder and the rubber.

[0038] (3) The present invention achieves adsorption and encapsulation modification and surface chemical modification of the graphene / N110 carbon black / high specific surface white carbon black powder surface by adding silane coupling agent, nano-sized zinc methacrylate, liquid rubber, and peroxide initiator to graphene, carbon black, and white carbon black for reaction and modification, thereby forming a novel three-phase composite material (i.e., mixed powder), in which one end of the silane coupling agent can chemically react with the rubber matrix, and the surface-coated liquid rubber can improve the compatibility of the composite material with the matrix rubber, thereby improving the wear resistance and tear resistance of the tread rubber. The alkoxy group at the other end of the silane coupling agent can undergo a hydrolysis reaction and undergo a condensation reaction with the hydroxyl group and other groups on the surface of the graphene / N110 carbon black / white carbon black to form a chemical bond or hydrogen bond, thereby improving the dispersibility of the graphene / N110 carbon black / white carbon black powder in the rubber matrix.

[0039] (4) The tread rubber of the present invention has a simple preparation process and can be prepared by only basic processes such as plasticizing, banburying, and thin-passing, etc., with low cost and applicable to industrial production. DETAILED DESCRIPTION

[0040] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.

[0041] The first aspect of the present invention is to provide a highly wear-resistant and tear-resistant tire tread rubber, which is prepared from the following raw materials in parts by weight: 100 parts of natural rubber, 70-80 parts of mixed powder, 4-6 parts of zinc oxide, 3-5 parts of antioxidant, 1-3 parts of dispersant, 1-3 parts of accelerator, 0.1-1 part of scorch retarder, and 1-2 parts of sulfur.

[0042] Preferably, the highly wear-resistant and tear-resistant tire tread rubber is made from the following raw materials in parts by weight: 100 parts of natural rubber, 74 to 79.6 parts of mixed powder, 5 parts of zinc oxide, 4 parts of antioxidant, 1.5 parts of dispersant, 2 parts of accelerator, 0.5 parts of anti-scorch agent, and 1.6 parts of sulfur.

[0043] The mixed powder is prepared from graphene, carbon black, white carbon black, a silane coupling agent, nano-grade zinc methacrylate, liquid rubber and a peroxide initiator.

[0044] The mass ratio of the graphene, carbon black, white carbon black, silane coupling agent, zinc methacrylate, liquid rubber and peroxide initiator is (3-10): (22-30): (18-27): (4-7): (3-9): (7-12): (0.3-0.7).

[0045] Preferably, the mass ratio of the graphene, carbon black, white carbon black, silane coupling agent, zinc methacrylate, liquid rubber and peroxide initiator is (5-8): (25-27): (20-25): (5.5-6): (5-8): (8-10): (0.5-0.6).

[0046] The carbon black is preferably N110 series carbon black.

[0047] The white carbon black has a specific surface area greater than 200 m 2 / g of high specific surface area white carbon black, preferably with a specific surface area of ​​200 to 235 m 2 / g high specific surface area white carbon black.

[0048] The silane coupling agent is selected from one or more of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, bis-[γ-(triethoxysilyl)propyl]disulfide, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane.

[0049] Preferably, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide or γ-mercaptopropyltrimethoxysilane.

[0050] The zinc methacrylate is preferably nano-scale zinc methacrylate.

[0051] The liquid rubber is selected from one or more of liquid isoprene, liquid butadiene, liquid styrene butadiene, and liquid ethylene propylene.

[0052] Preferably, the liquid rubber is liquid isoprene or liquid butadiene.

[0053] The peroxide initiator is selected from one or more of dicumyl peroxide, 1,4-di-tert-butyl peroxycumene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0054] Preferably, the peroxide initiator is dicumyl peroxide or 1,4-di-tert-butyl peroxycumene.

[0055] The antioxidant is selected from one or more of N-cyclohexyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and 2-thiol benzimidazole.

[0056] Preferably, the antioxidant is obtained by mixing N-cyclohexyl-N'-phenyl-p-phenylenediamine and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine in a mass ratio of 1:1.

[0057] The dispersant is selected from one or both of microcrystalline wax and paraffin wax.

[0058] Preferably, the dispersant is microcrystalline wax or paraffin.

[0059] The accelerator is selected from one or more of N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, 2-thiol benzothiazole, diphenylguanidine, benzothiazole disulfide, and tetramethylthiuram disulfide.

[0060] Preferably, the accelerator is one or both of N-tert-butyl-2-benzothiazolylsulfenamide and N-cyclohexyl-2-benzothiazolylsulfenamide.

[0061] More preferably, the accelerator is a mixture of N-tert-butyl-2-benzothiazolyl sulfenamide and N-cyclohexyl-2-benzothiazolyl sulfenamide, and the mass ratio of N-tert-butyl-2-benzothiazolyl sulfenamide to N-cyclohexyl-2-benzothiazolyl sulfenamide is 1:1.

[0062] The scorch retarder is preferably N-cyclohexylthiophthalimide.

[0063] The second aspect of the present invention is to provide a method for preparing the high wear-resistant and high tear-resistant tire tread rubber according to the first aspect of the present invention, the preparation method comprising the following steps:

[0064] Step 1, plasticizing the natural rubber, then adding zinc oxide, antioxidant, dispersant, accelerator, and anti-scorch agent for banburying, then adding the mixed powder for further banburying, and removing the rubber to obtain a film;

[0065] Step 2: Re-refining the rubber sheet obtained in step 1, then adding sulfur and accelerator to turn the rubber sheet left and right, and finally thinning it to obtain tire tread rubber.

[0066] The above steps are described in detail below.

[0067] In step 1, the mixed powder is prepared by the following steps:

[0068] Step a, adding graphene, carbon black and white carbon black into water and stirring to obtain a mixed solution, adding a silane coupling agent into a mixed solvent of ethanol, water and acetic acid, stirring to obtain a hydrolyzate, adding the hydrolyzate into the mixed solution to react, after the reaction is completed, filtering to obtain a solid, and drying to obtain a powder solid;

[0069] Step b: mixing and stirring the powder solid and zinc methacrylate, and then adding liquid rubber and peroxide initiator and continuing to stir and mix to obtain a mixed powder.

[0070] Preferably, in step a, graphene, carbon black and white carbon black are added to water, and stirred and mixed at a stirring speed of 1500 to 2500 r / min and a temperature of 50 to 70° C. to obtain a mixed solution.

[0071] Preferably, graphene, carbon black and white carbon black are added into water, and stirred and mixed at a stirring speed of 2000 r / min and a temperature of 60° C. to obtain a mixed solution.

[0072] Ethanol and water are mixed in a volume ratio of (150-250): (100-150), and then acetic acid is added to adjust the pH to 3.5-4.5. A silane coupling agent is slowly added to the obtained mixed solvent, and the mixture is stirred at a stirring speed of 300-700 r / min until the solution becomes clear to obtain a hydrolyzate.

[0073] Preferably, ethanol and water are mixed in a volume ratio of (150-250): (100-150), and then acetic acid is added to adjust the pH to 4, and a silane coupling agent is slowly added to the obtained mixed solvent, and stirred at a stirring speed of 500 r / min until the solution becomes clear to obtain a hydrolyzate.

[0074] The hydrolyzate is slowly added to the mixed solution, reacted at 50-70° C. for 1-3 hours, filtered to obtain a solid, and then dried at 100-120° C. for 1-3 hours to obtain a powder solid.

[0075] Preferably, the hydrolyzate is slowly added to the mixed solution, reacted at 60° C. for 2 h, filtered to obtain a solid, and then dried at 110° C. for 2 h to obtain a powdered solid.

[0076] Preferably, in step b, zinc methacrylate is added to the powder solid at 90-110° C. and a stirring speed of 2500-3500 r / min, and mixed and stirred for 20-45 min, and then liquid rubber and peroxide initiator are added and mixed and stirred for another 20-45 min to obtain a mixed powder.

[0077] Preferably, at 100° C. and a stirring speed of 3000 r / min, zinc methacrylate is added to the powder solid, mixed and stirred for 30 minutes, and then liquid rubber and peroxide initiator are added and mixed and stirred for another 30 minutes to obtain a mixed powder.

[0078] Graphene used in the present invention is a kind of carbon atom in sp 2 A two-dimensional carbon nanomaterial composed of hexagonal honeycomb lattices composed of hybrid orbitals. Graphene has excellent optical, electrical, and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery. It is considered to be a revolutionary material in the future. The high structure of graphene can improve the mechanical properties and wear resistance of rubber, but graphene has a very high specific surface area and is a light and easily flying powder, which makes it difficult to disperse graphene in rubber, resulting in a decrease in rubber performance, and it is easy to cause environmental pollution during processing.

[0079] N110 series carbon black has small particle size, large surface area, and can generate more bonding glue with rubber, which can give rubber the best wear resistance. High specific surface area white carbon black (specific surface area greater than 200m 2 / g) can improve the tear resistance of rubber, but N110 series carbon black and high specific surface white carbon black have poor dispersibility in rubber and poor processing technology.

[0080] In order to solve the above problems, the present invention first pre-treats graphene, N110 series carbon black and high specific surface white carbon black to obtain a novel three-phase composite material (i.e., the mixed powder of the present invention). The composite material is not only easily dispersed in the rubber matrix, but also can retain the excellent properties of graphene, N110 series carbon black and high specific surface white carbon black, which not only solves the problems of poor dispersion and poor processing technology of graphene, N110 series carbon black and high specific surface white carbon black in rubber, but also can greatly improve the wear resistance, tear strength, tensile strength and elongation at break of tire tread rubber, thereby improving the use performance of tire tread rubber.

[0081] The natural rubber is plasticized at 60-70 r / min and 60-80°C for 1-3 min, and then zinc oxide, antioxidant, dispersant, accelerator and anti-scorch agent are added and kneaded for 1-3 min. Subsequently, the mixed powder is added and kneaded for 1-3 min. The temperature is raised to 140-160°C for debonding to obtain a rubber sheet.

[0082] Preferably, the natural rubber is plasticized at 65 r / min and 70° C. for 1.5 min, and then zinc oxide, antioxidant, dispersant, accelerator and anti-scorch agent are added and kneaded for 2 min, and then the mixed powder is added and kneaded for 2 min, and the temperature is raised to 150° C. for debonding to obtain a film.

[0083] In step 2, the roller spacing of the mixing mill is adjusted to 1-2 mm, the rubber sheet obtained in step 1 is re-refined 1-4 times, rolled, sulfur and accelerator are added, the rubber sheet is turned over 2-4 times on each side, and then the roller spacing of the mixing mill is adjusted to 0.1-0.3 mm and thinned 5-9 times to obtain tire tread rubber.

[0084] Preferably, the roller spacing of the mixing mill is adjusted to 1.5 mm, the rubber sheet obtained in step 1 is re-refined 2 to 3 times, rolled, sulfur and accelerator are added, and the rubber sheet is turned over 3 times on each side, and then the roller spacing of the mixing mill is adjusted to 0.2 mm and thinned 6 to 8 times to obtain tire tread rubber.

[0085] Example

[0086] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.

[0087] Example 1

[0088] Weigh 5 g of graphene, 25 g of N110 carbon black, and 200 m 2 / g of white carbon black 25g, add to a beaker containing 2000ml of deionized water under high-speed stirring, the stirrer speed is 2000r / min, and the beaker is placed in a constant temperature water bath at a temperature of 60°C. Use a beaker to measure 150 ml of ethanol and 100 ml of deionized water, add acetic acid to adjust the pH to 4, slowly add 5.5g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, stir with a stirrer at a stirring speed of 500r / min until the solution becomes clear, and obtain a hydrolyzate of bis-[γ-(triethoxysilyl)propyl]tetrasulfide. Slowly add the hydrolyzate to the mixed solution of graphene / N110 series carbon black / white carbon black and react at a constant temperature of 60°C for 2h, then filter to obtain a powder solid, and dry the powder solid at 110°C for 2h for standby use.

[0089] The obtained powder solid is added to a high-speed mixer at a temperature of 100°C, the speed of the high-speed mixer is increased to 3000r / min, and then 5 grams of nano-grade zinc methacrylate is added, stirred for 30 minutes, and then 0.5 grams of diisopropylbenzene peroxide is added, and 8 grams of liquid isoprene is added and mixed for 30 minutes, so that the several materials in the mixer undergo ionization reaction to obtain a mixed powder (three-phase composite material) for use.

[0090] Weigh 100 g of natural rubber, 74 g of the mixed powder obtained in the above steps, 5 g of zinc oxide, 1.5 g of dispersant, 4 g of antioxidant, 2 g of accelerator, 0.5 g of anti-scorch agent and 1.6 g of sulfur for later use.

[0091] The antioxidant is a mixture of N-cyclohexyl-N'-phenyl-p-phenylenediamine and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine in a mass ratio of 1:1, the dispersant is microcrystalline wax, the accelerator is N-tert-butyl-2-benzothiazolylsulfonamide, and the anti-scorch agent is N-cyclohexylthiophthalimide.

[0092] The speed of the internal mixer was set to 65r / min, and the temperature was adjusted to 70°C. The natural rubber was then put into the internal mixer for plasticization for 1.5min. Zinc oxide, antioxidant, dispersant, anti-scorch agent, and part of the accelerator were then added in sequence and mixed for 2min. The prepared graphene / N110 series carbon black / white carbon black mixed powder was then added and mixed for another 2min. The rubber was discharged at about 150°C.

[0093] Adjust the roller spacing of the mixing mill to 1.5mm, re-mix the rubber sheet obtained by the internal mixer for 2-3 times, wrap the roller, then add sulfur and part of the accelerator, turn the rubber left and right three times each, then adjust the roller spacing of the mixing mill to 0.2mm and make a thin pass 6-8 times, produce the sheet according to the required thickness and size, and leave it for 12 hours to obtain the tire tread rubber; then perform vulcanization test on the performance, and the vulcanization conditions are 150℃×30min.

[0094] Example 2

[0095] Weigh 8 g of graphene, 27 g of N110 carbon black, and a specific surface area of ​​235 m 2 / g of white carbon black 20g, add it into a beaker containing 2500ml of deionized water under high-speed stirring, the stirrer speed is 2000r / min, and the beaker is placed in a constant temperature water bath at a temperature of 60°C. Use a beaker to measure 250ml of ethanol and 150ml of deionized water, add acetic acid to adjust the pH to 4, slowly add 6g of γ-mercaptopropyltrimethoxysilane, stir with a stirrer at a stirring speed of 500r / min until the solution becomes clear, and obtain the hydrolyzate of γ-mercaptopropyltrimethoxysilane, add the hydrolyzate into the mixed solution of graphene / N110 series carbon black / white carbon black, react at a constant temperature of 60°C for 2h, then filter to obtain a powder solid, and dry the powder solid at 110°C for 2h for standby use.

[0096] The obtained powder solid is added to a high-speed mixer at a temperature of 100°C, the speed of the high-speed mixer is increased to 3000r / min, and then 8 grams of nano-grade zinc methacrylate is added, stirred for 30 minutes, and then 0.6 grams of 1,4-di-tert-butylperoxyisopropylbenzene is added, and 10 grams of liquid butadiene is added and mixed for 30 minutes, so that the several materials in the mixer undergo ionization reaction to obtain a mixed powder (three-phase composite material) for use.

[0097] Weigh 100 g of natural rubber, 79.6 g of the mixed powder obtained in the above steps, 5 g of zinc oxide, 1.5 g of dispersant, 4 g of antioxidant, 2 g of accelerator, 0.5 g of anti-scorch agent and 1.6 g of sulfur for later use.

[0098] The antioxidant is a mixture of N-cyclohexyl-N'-phenyl-p-phenylenediamine and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine in a mass ratio of 1:1, the dispersant is paraffin, the accelerator is a mixture of N-cyclohexyl-2-benzothiazole sulfonamide and N-tert-butyl-2-benzothiazole sulfonamide in a mass ratio of 1:1, and the anti-scorch agent is N-cyclohexylthiophthalimide.

[0099] Set the speed of the internal mixer to 65r / min and the temperature to 70°C, then put the natural rubber into the internal mixer and plasticize for 1.5 minutes, then add zinc oxide, antioxidant, dispersant, and accelerator in turn and mix for 2 minutes, then add the prepared graphene / N110 series carbon black / white carbon black mixed powder, mix for another 2 minutes, and discharge the rubber at about 150°C.

[0100] Adjust the roller distance of the mixing mill to 1.5mm, re-mix the rubber sheet obtained by the internal mixer for 2-3 times, wrap the roller, then add sulfur and accelerator, turn the rubber left and right three times each, then adjust the roller distance of the mixing mill to 0.2mm and make thin passes 6-8 times, produce the sheet according to the required thickness and size, and leave it for 12 hours to obtain the tire tread rubber. Then perform the vulcanization test performance, the vulcanization condition is 150℃×30min.

[0101] Comparative Example

[0102] Comparative Example 1

[0103] The preparation was carried out in a manner similar to that of Example 1, except that no mixed powder was prepared and 55 g of N110 series carbon black was used instead of 74 g of mixed powder.

[0104] Comparative Example 2

[0105] The preparation was carried out in a manner similar to that of Example 1, except that no mixed powder was prepared and 55 g of a 200 m 2 / g of white carbon black replaces 74 grams of mixed powder.

[0106] Comparative Example 3

[0107] The preparation was carried out in a similar manner to Example 1, except that: no mixed powder was prepared, 5 g of graphene, 25 g of N110 carbon black, and 25 g of carbon black with a specific surface area of ​​200 m 2 / g of white carbon black, replacing 74 grams of mixed powder.

[0108] Experimental example

[0109] Experimental Example 1 Mechanical Properties Test

[0110] The products obtained in Examples 1 to 2 and Comparative Examples 1 to 3 were respectively subjected to tensile strength, tear strength, elongation at break and Akron abrasion tests. The test results are shown in Table 1.

[0111] Table 1

[0112]

[0113]

[0114] It can be seen from Table 1 that the tensile strength, tear strength and elongation at break of the tread rubbers prepared in Examples 1 to 2 of the present invention are higher than those of the tread rubbers prepared in Comparative Examples 1 to 3, and the Akron abrasion of the tread rubbers prepared in Examples 1 to 2 is lower than that of the tread rubbers prepared in Comparative Examples 1 to 3, indicating that the tread rubber of the present invention has both higher mechanical properties and lower wear.

[0115] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A highly wear-resistant and tear-resistant tire tread rubber, characterized in that: The high wear-resistant and tear-resistant tire tread rubber is prepared from the following raw materials in parts by weight: 100 parts of natural rubber, 70-80 parts of mixed powder, 4-6 parts of zinc oxide, 3-5 parts of antioxidant, 1-3 parts of dispersant, 1-3 parts of accelerator, 0.1-1 part of scorch retarder and 1-2 parts of sulfur.

2. The high wear-resistant and tear-resistant tire tread rubber according to claim 1, characterized in that: The high wear-resistant and tear-resistant tire tread rubber is prepared from the following raw materials in parts by weight: 100 parts of natural rubber, 74-79.6 parts of mixed powder, 5 parts of zinc oxide, 4 parts of antioxidant, 1.5 parts of dispersant, 2 parts of accelerator, 0.5 parts of anti-scorch agent and 1.6 parts of sulfur.

3. The high wear-resistant and tear-resistant tire tread rubber according to claim 1, characterized in that: The mixed powder is prepared from graphene, carbon black, white carbon black, silane coupling agent, nano-sized zinc methacrylate, liquid rubber and peroxide initiator; The mass ratio of the graphene, carbon black, white carbon black, silane coupling agent, zinc methacrylate, liquid rubber and peroxide initiator is (3-10): (22-30): (18-27): (4-7): (3-9): (7-12): (0.3-0.7).

4. The high wear-resistant and tear-resistant tire tread rubber according to claim 3, characterized in that: The white carbon black has a specific surface area greater than 200 m 2 / g of white carbon black; and / or, The silane coupling agent is selected from one or more of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, bis-[γ-(triethoxysilyl)propyl]disulfide, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane; and / or, The liquid rubber is selected from one or more of liquid isoprene, liquid butadiene, liquid styrene butadiene, and liquid ethylene propylene; and / or, The peroxide initiator is selected from one or more of dicumyl peroxide, 1,4-di-tert-butyl peroxycumene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

5. The high wear-resistant and tear-resistant tire tread rubber according to claim 1, characterized in that: The antioxidant is selected from one or more of N-cyclohexyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and 2-thiol benzimidazole; and / or, The dispersant is selected from one or both of microcrystalline wax and paraffin; and / or, The accelerator is selected from one or more of N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, 2-thiol benzothiazole, diphenylguanidine, benzothiazole disulfide, and tetramethylthiuram disulfide; and / or, The anti-scorch agent is N-cyclohexylthiophthalimide.

6. A method for preparing the highly wear-resistant and tear-resistant tire tread rubber according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Step 1, plasticizing the natural rubber, then adding zinc oxide, antioxidant, dispersant, accelerator, and anti-scorch agent for banburying, then adding the mixed powder for further banburying, and removing the rubber to obtain a film; Step 2: Re-refining the rubber sheet obtained in step 1, then adding sulfur and accelerator to turn the rubber sheet left and right, and finally thinning it to obtain tire tread rubber.

7. The preparation method according to claim 6, characterized in that: In step 1, the mixed powder is prepared by the following steps: Step a, adding graphene, carbon black and white carbon black into water and stirring to obtain a mixed solution, adding a silane coupling agent into a mixed solvent of ethanol, water and acetic acid, stirring to obtain a hydrolyzate, adding the hydrolyzate into the mixed solution to react, after the reaction is completed, filtering to obtain a solid, and drying to obtain a powder solid; Step b: mixing and stirring the powder solid and zinc methacrylate, and then adding liquid rubber and peroxide initiator and continuing to stir and mix to obtain a mixed powder.

8. The preparation method according to claim 7, characterized in that: In step a, Adding graphene, carbon black and white carbon black into water, stirring and mixing at a stirring speed of 1500 to 2500 r / min and a temperature of 50 to 70° C. to obtain a mixed solution; and / or, Mixing ethanol and water in a volume ratio of (150-250): (100-150), then adding acetic acid to adjust the pH to 3.5-4.5, slowly adding a silane coupling agent to the obtained mixed solvent, stirring at a stirring speed of 300-700 r / min until the solution becomes clear, to obtain a hydrolyzate; and / or, Slowly adding the hydrolyzate to the mixed solution, reacting at 50-70° C. for 1-3 hours, filtering to obtain a solid, and then drying at 100-120° C. for 1-3 hours to obtain a powder solid; and / or, In step b, zinc methacrylate is added to the powder solid at 90-110° C. and a stirring speed of 2500-3500 r / min, and the mixture is mixed and stirred for 20-45 minutes. Subsequently, liquid rubber and peroxide initiator are added and the mixture is mixed and stirred for 20-45 minutes to obtain a mixed powder.

9. The preparation method according to claim 6, characterized in that: In step 1, The natural rubber is plasticized at 60-70 r / min and 60-80°C for 1-3 min, and then zinc oxide, antioxidant, dispersant, accelerator and anti-scorch agent are added and kneaded for 1-3 min. Subsequently, the mixed powder is added and kneaded for 1-3 min. The temperature is raised to 140-160°C for debonding to obtain a rubber sheet.

10. The preparation method according to claim 6, characterized in that: In step 2, Adjust the roller distance of the mixing mill to 1-2 mm, re-refine the rubber sheet obtained in step 1 for 1-4 times, wrap the roller, add sulfur and accelerator, turn the rubber sheet 2-4 times on each side, and then adjust the roller distance of the mixing mill to 0.1-0.3 mm and pass the thin rubber sheet 5-9 times to obtain the tire tread rubber.

Citation Information

Patent Citations

  • A kind of preparation method of high wear-resistant tire tread rubber

    CN106279853B

  • High-wear-resistance tire tread rubber

    CN110713630A